Carbon‐Based Materials for Articular Tissue Engineering: From Innovative Scaffolding Materials toward Engineered Living Carbon. Issue 1 (12th October 2021) - Islam, Monsur; Lantada, Andrés Díaz; Mager, Dario; Korvink, Jan G.
Abstract: Carbon materials constitute a growing family of high‐performance materials immersed in ongoing scientific technological revolutions. Their biochemical properties are interesting for a wide set of healthcare applications and their biomechanical performance, which can be modulated to mimic most human tissues, make them remarkable candidates for tissue repair and regeneration, especially for articular problems and osteochondral defects involving diverse tissues with very different morphologies and properties. However, more systematic approaches to the engineering design of carbon‐based cell niches and scaffolds are needed and relevant challenges should still be overcome through extensive and collaborative research. In consequence, this study presents a comprehensive description of carbon materials and an explanation of their benefits for regenerative medicine, focusing on their rising impact in the area of osteochondral and articular repair and regeneration. Once the state‐of‐the‐art is illustrated, innovative design and fabrication strategies for artificially recreating the cellular microenvironment within complex articular structures are discussed. Together with these modern design and fabrication approaches, current challenges, and research trends for reaching patients and creating social and economic impacts are examined. In a closing perspective, the engineering of living carbon materials is also presented for the first time and the related fundamental breakthroughs ahead are clarified. Abstract : Carbon‐based solutions in the area of osteochondral and articular repair and regeneration are emphasized by comprehensively reviewing the application of different carbon allotropes and the fabrication strategies employed to achieve the carbon scaffolds. Different challenges of the carbon‐based scaffolds are discussed toward clinical applications. A futuristic vision for engineering of carbon‐based living materials is laid out as a promising future direction.